Dacryopinax (Fungi: Dacrymycetales) in Mexico - Castro-Santiuste, Sandra; Sierra, Sigfrido; Guzmán-Dávalos, Laura; Cifuentes, Joaquín; Evans, Thomas; Martínez-González, César Ramiro; Alvarado-Sizzo, Hernán; Luna-Vega, Isolda (Phytotaxa, 2020)
A taxonomical revision of the Dacryopinax species in Mexico is presented in detail. Historically, only four species were known in the country: Dacryopinax elegans, D. lowyi, D. spathularia, and D. yungensis. Dacryopinax martinii is reported for the first time from Mexico. Taxonomical descriptions and remarks for all the species, based on macro- and micro-morphology, as well as geographical distribution are included, except for D. yungensis, as its record corresponded to a misidentification of D. spathularia. We propose a new phylogeny including the taxonomic position and relationships of all species, based on ITS and LSU sequence data. Finally, a dichotomous key to identify the four species in Mexico is provided.